ANALYSIS OF FISCAL CAPACITY ON HUMAN DEVELOPMENT INDEX WITH MANDATORY SPENDING ON EDUCATION AND HEALTH AS INTERVENING VARIABLE (AN EMPIRICAL STUDY ON REGENCIES/CITIES IN JAVA) - Andy Dwi Bayu Bawono; Heppy Purbasari; Mujiyati Mujiyati (Muhammadiyah International Journal of Economics and Business, 2018)
Regional  autonomy  is  aimed  at  enhancing  the proximity  between  the  local  government  and  its people,  in  terms the local  government  will  identify  the  weaknesses and strengths of  its  area  from the highest to lowest  level. This  research attempts to  find  out  the influence  of  the  Fiscal  Capacity Index on the Human Development Index with mandatory spending on education and health as the intervening  variables.  The  research used   empirical  and  explanatory  research method  to  analyze the fiscal capacity  index  on the intervening  variables. This  study  involved  secondary data,  which were obtained  from  certain  agencies,  namely  the Regulation  of  Minister  of  Finance  (PMK  No.119/PMK.07/2017), the GRDP Realization  Report  of  Regencies/Cities  in  Java Fiscal Year  2016,  and the data published by the Central Bureau of Statistics of Regencies/Cities in Java in 2017. The results of  the hypothesis  analysis reveal that the  fluctuation  in  the Fiscal  Capacity  Index  in  each region is able to influence the amount of mandatory spending in education and health. Meanwhile, the Path  Analysis  test indicates  that the  Fiscal  Capacity  Index  has a  stronger influence  on  the Human   Development Index without any   intervention   from   mandatory   spending   on   education and  health.  Essentially, the Fiscal  Capacity  Index  is  the main  variable  that  affects the Human Development  Index.